Hormonal contraception in women with polycystic ovary syndrome: Contraceptive and non-contraceptive effects. A clinical lecture - Olga A. Pustotina (Гинекология)
The clinical diversity of polycystic ovary syndrome (PCOS) makes the diagnosis challenging, leaving many women untreated. The article deals in detail with the PCOS diagnosis algorithm and pathogenesis, as well as the adverse impact of PCOS on the reproductive and overall health of women. The necessity of using combined hormonal contraception both to prevent unwanted pregnancy and to reduce the risks associated with PCOS is justified, and the advantages of a chlormadinone-containing combined oral contraceptive in women with hyperandrogenism are given.